Direito de proteção à diversidade cultural musical: a música eletrônica e o DJ - Martignago, Gisella (2014)
Law and music are topics of great richness and complexity. However, the relationship between these two fields of human knowledge and culture is not usually explored by scientific researchers of both universes. This thesis aims to analyze the electronic music DJ and work from the perspective of Cultural Rights. Moreover describe that meets our legal system is flawed as the understanding and regulation of the activity and creations of artists DJs Proof of this position lies in the impossibility of this hold the record of his musical work nor their work is regulated by labor laws. At the moment we accept and regulate this artistic activity, freedom of musical expression and musical cultural diversity will be strengthened